Growth to Limits of Female Labor Participation in Latin America’s Unequal Care Regime - Martínez Franzoni, Juliana (2019)
Throughout Latin America, legal barriers enabling women to make a living equal to men are largely gone. However, women continue to lag behind men in gaining access to economic resources, and women’s labor participation differs significantly across class lines. Drawing on a policy-based explanation, we argue that a primary reason why the removal of legal barriers is insufficient for women’s economic empowerment due to the presence of a socially unequal care regime, one that sits at the intersection of high-income inequality and the absence of universal care services.